(untitled) (Journal of actual problems of jurisprudence, 2018)
The article discusses some of the legal problems of payment for the use of groundwater in the transition to a «green» economy. The features of groundwater as an object of regulation and a study of economic instruments regulating the protection and use of groundwater, the ways of improvement of legislation in the field of study. Key words: legal regulation, environmental charges, ground water, environment, nature.